2007
DOI: 10.1016/j.physbeh.2007.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of fear tests used on cattle, pigs, sheep, poultry and horses

Abstract: FORKMAN, B., A., BOISSY, M.-C., SALAÜN, E., CANALI, AND R.B., JONES. A critical review of fear tests used on cattle, pigs, sheep, poultry and horses. PHYSIOL. BEHAV. 000-000, 2007. Fear is arguably the most commonly investigated emotion in domestic animals. In the current review we attempt to establish the level of repeatability and validity found for fear tests used on cattle, pigs, sheep and goats, poultry and horses. We focus the review on the three most common types of fear tests: the arena test (open fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
654
6
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 753 publications
(701 citation statements)
references
References 151 publications
(222 reference statements)
18
654
6
23
Order By: Relevance
“…In animals kept for production, both environmental challenges and social isolation are recognised as stressors, which could negatively affect the fear and anxiety levels of the animals (Forkman et al, 2007) and thus their physiology and immune reaction (Koolhaas et al, 1999). Specific tests are used to measure fear levels in several species (Forkman et al, 2007), but few experimental data are available for rabbits (Verga et al, 2007): the tonic immobility test has been used to evaluate rabbit fear towards humans (Ferrante et al, 1992;Trocino et al, 2004 andVerwer et al, 2009), and the open-field test has been used to obtain information on the fear of rabbits when exposed to an unknown environment (Meijsser et al, 1989;Ferrante et al, 1992;Xiccato et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In animals kept for production, both environmental challenges and social isolation are recognised as stressors, which could negatively affect the fear and anxiety levels of the animals (Forkman et al, 2007) and thus their physiology and immune reaction (Koolhaas et al, 1999). Specific tests are used to measure fear levels in several species (Forkman et al, 2007), but few experimental data are available for rabbits (Verga et al, 2007): the tonic immobility test has been used to evaluate rabbit fear towards humans (Ferrante et al, 1992;Trocino et al, 2004 andVerwer et al, 2009), and the open-field test has been used to obtain information on the fear of rabbits when exposed to an unknown environment (Meijsser et al, 1989;Ferrante et al, 1992;Xiccato et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits kept in individual and bicellular cages showed a higher latency to enter the arena, which has been validated as the best indicator of general fear (Forkman et al, 2007), whereas rabbits in collective cages showed more 'bold' behaviours (running, biting and rearing). According to Schepers et al (2009), solitary-housed pet rabbits appeared more fearful during the open-field test compared with rabbits kept in groups.…”
mentioning
confidence: 99%
See 3 more Smart Citations